Artificial intelligence : applications and innovations - Priyadarshini, Rashmi (Boca Raton, FL : Chapman & Hall/CRC Press, 2023)
"Artificial Intelligence : applications and innovations is a book about the science of artificial intelligence (AI). AI is the study of the design of intelligent computational agents. This book provides a valuable resource for researchers, scientists, professionals, academicians and students dealing with the new challenges and advances in the areas of artificial intelligence and innovations. This book also covers a wide range of applications of machine learning such as fire detection, structural health and pollution monitoring and control. Key features : provides insight into prospective research and application areas related to industry and technology, discusses industry-based inputs on success stories of technology adoption, discusses technology applications from a research perspective in the field of artificial intelligence, and provides a hands-on approach and case studies for readers of the book to practice and assimilate learning. This book is primarily aimed at graduates and post-graduates in computer science, information technology, civil engineering, electronics and electrical engineering and management"--
Machine learning- principles and algorithms / Gagandeep Kaur, Satish Saini and Amit Sehgal -- Applications of machine learning and deep learning / Gagandeep Kaur, Satish Saini and Amit Sehgal -- Environmental monitoring in WSN using AI / Arpana Mishra and Rashmi Priyadarshini.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence; Artificial intelligence -- Industrial applications; COMPUTERS / Machine Theory